Nic Juliana Tuwima (dwie wykładnie) - Wójcik, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
The article discusses fragments of poems by Julian Tuwim from the volume Rzecz Czarnoleska: poem Fryzjerzy [Barbers] and prose poem Skrzydlaty złoczyńca [Winged Criminal]. Based on these poems, different meanings of the concept of “nothing” are considered: modern (social, urban, twentieth-century) and universal (philosophical, ontological, metaphysical). Analysis of these meanings reveals in Tuwim’s poetry a melancholic vision of the city and a concept of existence close to existentialism.